Synthesis, functionalization and applications of silver nanoparticles - Ledwith, Deirdre (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The aim of the work described in this thesis is to investigate various different methods for synthesis, functionalization and surface-enhanced Raman spectroscopy applications of silver nanoparticles.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.